Celecoxib inhibits metabolism of cytochrome P450 2D6 substrate metoprolol in humans - Werner, Ulrike; Werner, Dierk; Rau, Thomas; Fromm, Martin F; Hinz, Burkhard; Brune, Kay (Clinical pharmacology and therapeutics, 2003)
In vitro data have shown that celecoxib inhibits the metabolism of cytochrome P450 (CYP) 2D6 substrates. However, very limited data are available on the influence of cyclooxygenase 2 inhibitors on the disposition of CYP2D6 substrates in humans. Therefore the objective of this study was to examine the effect of celecoxib and rofecoxib on the pharmacokinetics of the clinically relevant CYP2D6 substrate metoprolol. An open, randomized, 3-period crossover study was performed in 12 healthy male volunteers. Metoprolol (50 mg) was given in all 3 periods without or after 7 days of pretreatment with celecoxib (200 mg twice daily) or rofecoxib (25 mg daily) to achieve steady-state conditions of cyclooxygenase 2 inhibitors in periods 2 and 3. Celecoxib significantly increased the area under the plasma concentration-time curve of metoprolol from 271 to 414 micro g. h/L (64% +/- 57%, P <.001) and by more than 200% in 1 volunteer. The extent of this drug interaction was more pronounced in volunteers with 2 fully functional alleles compared with volunteers with 1 fully functional allele (103% +/- 75% versus 36% +/- 23%, P <.05). After administration of celecoxib, the area under the plasma concentration-time curve from 0 to 24 hours of alpha-hydroxymetoprolol decreased significantly from 474 to 387 micro g. h/L (P <.01). Rofecoxib caused no significant effects on the pharmacokinetics of metoprolol. We conclude that celecoxib inhibits the metabolism of the CYP2D6 substrate metoprolol but that rofecoxib does not. Clinically relevant drug interaction may occur between celecoxib and CYP2D6 substrates, particularly those with a narrow therapeutic index.